Measuring pain in the newborn infant - Green, G (2018)
Hospitalised infants require multiple painful procedures a day as part of their essential medical care. However, identifying and managing pain in non-verbal populations is challenging – the gold standard in adults is self-report of pain, but in infants we must rely on surrogate measures. In this thesis, electroencephalography (EEG), behavioural measures and physiological changes are used to investigate infant pain responses, exploring how responses to noxious stimulation are modulated by analgesics, age and pathology. It is essential to validate measures of pain in infants. As pain is both an emotional and sensory experience, noxious-evoked brain activity likely provides an important surrogate pain measure. An EEG template of noxious-evoked brain activity was validated for use in an independent group of infants: the noxiousevoked brain activity was only elicited in response to noxious stimulation and not in response to stimulation of other sensory modalities; was correlated with pain-related behaviour; and was sensitive to analgesic modulation by the use of topical local anaesthetic. This provides a novel approach, which can be used to test analgesic efficacy in infants. Behavioural responses form the cornerstone of clinical infant pain assessment. However, it is not clear whether the youngest, most premature infants are able to mount behavioural responses that can discriminate between noxious and innocuous stimulation. In this thesis, I have investigated the behavioural response to noxious and tactile stimulation in infants from 28-41 weeks corrected gestational age (CGA). The youngest infants demonstrated a lack of behavioural discrimination, being equally likely to mount a behavioural response to a tactile or a noxious stimulus. Responses diverged with increasing age, such that from approximately 32 weeks’ gestation, infants were significantly more likely to display facial grimacing to noxious stimulation. Finally, the impact of pathology on pain experience has not been well studied. I have investigated how early life infection impacts pain-related responses and demonstrate, using a multidimensional approach, that infants with infection display significantly greater noxious-evoked brain activity and are more likely to mount a behavioural response compared with non-infected infants. In summary, this thesis demonstrates that responses to pain are altered by age and pathology, and provides a novel brain-derived approach to testing the efficacy of analgesic interventions in infants.